The impact of corporate governance on the restrictiveness of covenants in private debt contract - Abu Bakar, Intan Suryani; Mather, Paul; Tanewski, George (2012)
We examine the association between corporate governance and the restrictiveness of covenants used in U.S. private debt contracts. Both corporate governance and covenants have been shown to play a role in mitigating agency problems associated with debt, hence a relationship is expected between these two monitoring mechanisms. Accordingly we argue that, ceteris paribus, firms with stronger corporate governance will be perceived by debtholders to be less likely to engage in ex-post opportunism thereby reducing the need to use particularly restrictive covenants. Our cross-sectional analysis on a sample of new syndicated loans in the U.S private debt market indicates that both a corporate governance score and board independence are positively and significantly associated with covenant slack. Similarly, we find that independent directors’ financial expertise and covenants slack are positively related, but we find no evidence that slack is associated with ‘busy’ directors or CEO duality. Overall, the empirical evidence supports the hypothesis that debtholders perceive aspects of corporate governance to be beneficial and factor them in to their contracting decisions.